NILAI-NILAI SOSIAL PADA KEGIATAN ARISAN BULANAN DI DUSUN LEUWISAENG DESA SURUSUNDA KECAMATAN KARANGPUCUNG - BAYU SUDRAJAT; MASNGUDI MASNGUDI (J-EBI: Jurnal Ekonomi Bisnis Islam, 2021)
Abstract:   Arisan is a group of people who collect money regularly in each certain period. After the money is collected, one of the group members will come out as the winner. Determination of the winner is usually done by lottery, but there is also a social gathering group that determines the winner by agreement. Arisan as a means for the community to gather and interact among residents. By following the social gathering, it is hoped that relations between communities can be well and harmoniously established. This is because in arisan activities there are many social values that are felt by the community.This research is a field research with a qualitative approach. The method used in this research is descriptive method. In this study, the researcher explained more about the social values in arisan activities in Leuwisaeng Hamlet, Surusunda Village.The results showed that the community received many benefits from social gathering activities. The benefits obtained by the community in arisan activities are facilities for community socializing activities, means of delivering information, establishing friendships between residents, training the soul to give charity, training the soul to help help, building unity and integrity, training in saving and growing a sense of trust.Keywords: Arisan, Social Values, Society